2022
DOI: 10.30699/fhi.v11i1.374
|View full text |Cite
|
Sign up to set email alerts
|

Security, Privacy, and Confidentiality in Electronic Prescribing Systems: A Review Study

Abstract: Introduction: The use of electronic prescribing has identified as a strategically important policy to improve health care. Therefore, the purpose of this study was to review the issues related to security, privacy and privacy of electronic copying systems.Material and Methods: A comprehensive review of studies were conducted that published in English, free access to the full text of the article and without time limitation, by searching for keywords in keywords, title and abstract of studies in valid scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In general, many studies today support the increasing impact of telehealth services through technology [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]; Considering the positive result of using teleophthalmology in screening, monitoring, adherence to treatment and improving the clinical conditions of patients with various eye diseases and the lack of reporting of side effects in therapeutic and monitoring approaches based on telemedicine, it can be concluded that the use of telemedicine in eye disorders using high-quality equipment and using multiple technologies in combination cause maximum effect and efficiency. As a result, policy makers and planners in this field should work on maximizing the quality of tele-ophthalmology equipment.…”
Section: Discussionmentioning
confidence: 99%
“…In general, many studies today support the increasing impact of telehealth services through technology [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]; Considering the positive result of using teleophthalmology in screening, monitoring, adherence to treatment and improving the clinical conditions of patients with various eye diseases and the lack of reporting of side effects in therapeutic and monitoring approaches based on telemedicine, it can be concluded that the use of telemedicine in eye disorders using high-quality equipment and using multiple technologies in combination cause maximum effect and efficiency. As a result, policy makers and planners in this field should work on maximizing the quality of tele-ophthalmology equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have addressed the design of different MDSs or speech therapy information systems, including remote speech therapy based on different MDSs [19][20][21][22][23][24][25][26][27][28][29][30][31]. However, evidence-based speech therapy and the basic need for an integrated system in the initial step require the unification of basic infrastructure, including MDS.…”
Section: Introductionmentioning
confidence: 99%